Evaluation Of Medical Waste Management In Two Hospital Of Karbala Governorate 2024 - Seror Kadhim Hamza; Ali Daher Habeeb; Dunia Fawaz Mohammed (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: Medical waste (MW) includes various materials such as used needles and syringes, medications, body parts, diagnostic samples, blood, radioactive materials, synthetic compounds, medical gadgets, and surgical masks. Healthcare waste is a subset of overall waste generation. Hospital waste may be harmful or non-hazardous. Hazardous waste presents physical, chemical, and microbiological risks to both the general public and healthcare workers involved in its processing, treatment, and disposal. The pandemic has accelerated the development of solid medical waste, leading to rising concerns about its handling. This highlighted the challenges of medical waste management, such as separation, storage, and transportation. Materials and Methods: descriptive cross-sectional study conducted to assess the management of medical waste in two of Holy Karbala Governorate hospitals (Imam Hassan Al-Mujtaba Teaching Hospital, Imam Hussein Medical City), Data were collected by hospital field visits and direct interviews with medical waste management workers, officials, and health care providers using questionnaire. Results: It was documented that the two hospital trained there staff infrequently an as need and had sufficient but sometime not appropriate personal protective equipment. Both of hospital are segregate medical waste and had incinerator which used to burn medical waste.